Characterisation of defects generated during constant current InGaN-on-silicon LED operation - Made, Riko I (2017)
We studied the degradation of MOCVD-grown InGaN LEDs on Si substrates under constant current stressing. Characterisations using Deep Level Transient Spectroscopy and Electron Energy Loss Spectroscopy on active areas showed that the stressing had generated defects that have trap states at 0.26 eV below the conduction band edge (Ec – 0.26 eV) and that correlated with the active area's lower nitrogen content as compared to unstressed samples. The combination of Current-Voltage, Electroluminescence, Cathodoluminescence, and device simulations indicate that an increase in the density of these defects is correlated with an increase in the non-radiative carrier recombination that causes degradation in light emission. Preventing formation of these defects will be critical for improving InGaN-on-silicon LED reliability.